A review of the public-funded primary health care facilities for children in the pluralistic health care settings of Barbados, a Caribbean island. Issue 2 (9th June 2015) - Nielsen, Anders L.; Kumar, Alok
Abstract : Aim: The major objectives of this study were to evaluate the existing pediatrics health care service provisions and utilizations of the public polyclinics in Barbados. Furthermore, the aim was to assess if the existing manpower resources were adequate. Background: Barbados has a mixed health care system consisting of both a socialized and a private health care system. The Ministry of Health commissioned a needs assessment survey of the pediatrics primary health care at the public polyclinics. Methods: Primary data were collected through interviews with the public primary health care providers. Secondary data were collected from the Barbados Census Data and Ministry of Health statistics. Data were analyzed to assess the pediatrics primary health care service utilization and adequacy of existing resources at the polyclinics. Findings: In 2012, there were 62 934 visits from children <16 years of age to the public polyclinics in Barbados and this accounted for 39.1% of all visits (both adults and children) to the polyclinics. An overall 16.7% of the visits were from children less than five years old to the Well Child Clinic for immunization and for growth and development monitoring; 32% of all physician consultations at the polyclinics were for children <16 years. Utilization of health services by children at the polyclinics was 5245 visits/month. Given an expected monthly demand for 10 822 visits from children, the polyclinics serve 48.5% of the primary health care demand for children in Barbados. Conclusions: The public polyclinics play a pivotal role in the pluralistic primary health care system in Barbados. They fulfill nearly half of all the primary care demand and more importantly provides for almost the entire immunization demand, and thereby ensuring high coverage. The existing resources, if used optimally, would reduce the long consultation time observed in this setting, and thereby increase the capacity considerably.